Palliative Care: We should begin to Think - Rahman, AKM Mahbubur; Ahmad, Nezamuddin (Journal of Bangladesh College of Physicians and Surgeons, 2011)
DOI: 10.3329/jbsp.v29i1.7163 J Bangladesh Coll Phys Surg 2011; 29:1-2